The Digital Lifeline: Benefits of AI in Revolutionizing Emergency Medicine and Triage - Rasit, Dinc (Rasit Dinc Digital Health & AI Research, 2024)
The Emergency Department ED is the critical front line of healthcare, a high-stakes environment where rapid, accurate decision-making is paramount. Faced wit...
Keywords: Diagnostics; Artificial Intelligence; Healthcare Innovation; Patient Care; Machine Learning